Study of Chlorination Application in Tapioca Wastewater Cyanide Removal - Happy Mulyani; Maria Endah Prasadja (Waste Technology, 2014)
Tapioca wastewater contains a high concentration of organic matter and cyanide. Chlorination has known as one of alternative cyanide removal methods. The fact that must be an attention is carcinogenic compound such as Tri Halo Methane could be produced as byproduct chlorination of organic waste. This research aimed to determine condition of chlorination application in tapioca wastewater cyanide removal especially calcium hypochlorite dosage and pH thus meeting the criteria of the quality standard of waste and Tri Halo Methane identification. Efluent of chlorination using calcium hypochlorite dosage based on stoichiometry reaction between chlor and cyanide (mole ratio chlor:cyanide = 1:1) which carried out at pH operation 8 for 60 minutes has observed for cyanide content and Tri Halo Methane identification. Other variation of calcium hypochlorite dosage applied until meet the standart quality or lower cyanide content of effluent with no Tri Halo Methane detected. pH optimum determined from comparation of quality effluent of chlorination using calcium hypochlorite optimum dosage with variation pH operation 6, 7, 8. The results showed that the optimum condition for chlorination application in tapioca wastewater removal was 5,986 mg/L for calcium hypochlorite dosage (1,75 stoichiometry reaction) and 8 for pH operation. This chlorination condition able to reduce cyanide of 192 mg/L to 0,272 mg/L wuth no Tri Halo Methane detected in the effluent.